The new menopause : navigating your path through hormonal change with purpose, power, and facts - Haver, Mary Claire (Medical doctor) (Rodale, 2024)
"Menopause is inevitable, but suffering through it is not! This is the empowering approach to self-advocacy that pioneering women's health advocate Dr. Mary Claire Haver takes for women in the midst of hormonal change in The New Menopause. A comprehensive, authoritative book of science-backed information and lived experience, it covers every woman's needs: From changes in your appearance and sleep patterns to neurological, musculoskeletal, psychological, and sexual issues, a comprehensive A-Z toolkit of science-backed options for coping with symptoms. What to do to mediate the risks associated with your body's natural drop in estrogen production, including for diabetes, dementia, Alzheimer's, osteoporosis, cardiovascular disease, and weight gain. How to advocate and prepare for annual midlife wellness visits, including questions for your doctor and how to insist on whole life care. The very latest research on the benefits and side effects of hormone replacement therapy. Arming women with the power to secure vibrant health and well-being for the rest of their lives, The New Menopause is sure to become the bible of midlife wellness for present and future generations"--